Etika praktis Ibn Muqaffa’: Kedudukan akal sehat untuk transformasi etika pada Kitab Al-Adab al-Shagir wa al-Adab al-Kabir - Mohammad Mahpur; Mamlu’atul Hasanah; Ghozi Ahmad; Akhmad Kholil (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2022)
Abstract: Literary ethical literacy can be a potential for developing critical ethical awareness learned from literary arts activities. This study explores the inspiration of practical ethics developed by Ibn Muqaffa 'in the book Al-Adab al-Shagir wa al-Adab al-Kabir with literary characteristics. This research was conducted using the text analysis method on only one work of Al-Adab al-Shagir wa al-Adab al-Kabir with the stages of text collection, reading intact, selecting main sentences, finding keywords, and interpreting to contextualize ethical concepts. The results found that Ibn Muqaffa' encouraged that ethics could be accommodated using literary narratives. Ethics is subjective and relevant to the need for existential happiness that produces theological views, schools, and schools of thought. Critical reasoning is in line with literary constructions with the role of active sagacity in practical ethics. The implication is that Ibn Muqaffa's literature can inspire the development of ethical learning methods using literary narrative learning to increase the quality of life that is meaningful for everyone.Abstrak: Literasi etik sastrawi dapat menjadi potensi tumbuhnya kesadaran kritis etik yang dapat dipelajari dari kegiatan seni kesastraan. Penelitian ini bertujuan menggali transformasi etika praktis yang dikembangkan Ibnu Muqaffa’ di kitab Al-Adab al-Shagir wa al-Adab al-Kabir berciri sastra. Penelitian ini dilakukan dengan menggunakan metode analisis teks hanya pada satu karya Al-Adab al-Shagir wa al-Adab al-Kabir dengan tahap koleksi teks, pembacaan utuh, memilih kalimat utama, menemukan kata kunci, dan melakukan interpretasi untuk kontekstualisasi konsep etik. Hasil penelitian ditemukan bahwa Ibnu Muqaffa’ mendorong bahwa etika praktis dapat diwadahi menggunakan narasi sastrawi; etika praktis bersifat subyektif dan relevan dengan kebutuhan kebahagiaan eksistensial yang melahirkan pandangan, aliran, mazhab teologis; penalaran kritis sejalan dengan peran akal sehat aktif dalam etika praktis. Implikasinya, sastra Ibnu Muqaffa’ dapat mengilhami pengembangan metode pembelajaran etika secara praktis dengan menggunakan pembelajaran naratif sastrawi untuk menambah kualitas hidup yang bermakna bagi semua orang.